ENT 530 Social Media Portfolio: Eatme Cookies / Nur Fatin Nabila Zulkarnain - Zulkarnain, Nur Fatin Nabila (2021)
EatMe Cookies is our own product created by the owner itself. EatMe Cookies offers a cookies product food to give the sastisfaction of customers. It is affordable price of the product. Our main target audiences are children, teenagers, young adults and also the adults to buy and love this cookies products. EatMe Cookies marketing strategy is to emphasize the quality and price of product. The product also using high-quality dark chocolate to make sure that the cookies are delicious and have a premium taste. The product also offers postage and COD for those who stay in Kelantan. Thus, by developing this marketing strategy it will attract the customers to buy the homemade cookies. The management of EatMe Cookies is by Nur Fatin Nabila Binti Zulkarnain. I created Facebook to expand the business through social media and learn how to post in the Facebook to connect and communicate with the customers. This platform also use to post for business product, whether teaser post, soft sell and hard sell. I also raise my revenue atleast RM61 or above and prudent spending for my product to avoid profit falls. It also learns how to use eUsahawan Portal to record the sales through eUsahawan Portal. It was very tough for me to handle this business but I have learned and gain new knowledge about business through this assignment.